The transformation of the Afar Commons in Ethiopia: State coercion, diversification, and property rights change among pastoralists - Hundie, Bekele; Padmanabhan, Martina (University of Pennsylvania Press, 2011)
In this chapter we discuss two cases of pastoralist involvement in agriculture and investigate the challenges and opportunities of this transition. We focus on the drivers of crop production from a dual perspective: first, as an outcome of state coercion and, second, as a voluntary response to natural calamities. Specifically, the chapter addresses the following questions: (1) Why was the Ethiopian government interested in transforming traditional communal rights at the beginning? How smooth or how rough was the process of change? (3) What are the outcomes in terms of property rights arrangements and pastoral livelihoods? (4) What factors explain pastoralists' responses to drought-induced changes? The first case portrays the conflictive transformation of the traditional land use arrangements of Afar pastoralists, which resulted from coercive state intervention aimed at expanding commercial farming, while the second case shows a nonconflictive change induced by recurrent droughts in the presence of support from the state.